Environmental industrial regulation and the private codes question - Gérard Mondello (Fondazione Eni Enrico Mattei (FEEM), 1997)
Self-regulation process is essentially based on contractual relationships. Several contract forms are coexisting. This paper is devoted to exemplify some of them specifically in the aim of giving an interpretation to the notion of private codes corresponding to self-commitment contracts, codes of behaviour, etc.. Theses codes are typically self-regulation. Based on contractual foundations, their understanding is quite complex. Several factors are at work explaining such complexity : their origin, the contract process between the agents and the enforcement of the contract itself. This paper is devoted mainly to understand how the implementation process of the private code may work. To deal with such a problem a matching repeated game has been used and the conditions which led to an equilibrium are studied. It appears that if some conditions are respected, as the definition of clear and credible threats, the ascertaining of the application of the private code, then such a regulation means may be proved efficient.
Keywords: 330